1984
DOI: 10.1515/bchm2.1984.365.2.703
|View full text |Cite
|
Sign up to set email alerts
|

The Light-Harvesting Polypeptides ofRhodopseudomonas sphaeroidesR-26.1. I. Isolation, Purification and Sequence Analyses

Abstract: Four low-molecular-mass polypeptides were isolated and purified from chromatophore membranes of Rhodopseudomonas spliaeroides blue-green mutant R-26.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…The resulting fractions 1 and 2 were purified by rechromatography under the same conditions. The highly purified polypeptides 1 and 2 had the amino acid compositions of the B870a and B800-850a polypeptides, respectively (33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting fractions 1 and 2 were purified by rechromatography under the same conditions. The highly purified polypeptides 1 and 2 had the amino acid compositions of the B870a and B800-850a polypeptides, respectively (33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…The N-and C-terminal domains of LH and RC polypeptides and the loops between the a helices of RC polypeptides are proposed to be exposed on the membrane surface (1,13,21,(36)(37)(38)(39). The primary structures of the LH and RC polypeptides from R. sphaeroides have been determined (2,26,(33)(34)(35)(36)(37)(38). LH * Corresponding author.…”
mentioning
confidence: 99%
“…Because there is only one copy of the B800-850-P polypeptide gene in the R. sphaeroides genome (27), it is likely that the difference between 15B and 15C is due to posttranslational events. Theiler et al (42,43) previously demonstrated heterogeneity in the amino termini of B800-850-P polypeptide; some contained amino-terminal methionine and the remainder had blocked amino-terminal threonine residues. This would be consistent with posttranslational modification of the P subunit.…”
Section: Discussionmentioning
confidence: 99%
“…The 7.4 kDa polypeptide shows the same three domain structures as the intramembrane antenna polypeptides of other purple bacteria [13][14][15][16][17][18][19] ( fig.4). As compared to the sequences of purple non-sulfur bacteria the 7.4 kDa polypeptide (65 amino acid residues) exhibits an extended Cterminal domain.…”
Section: Discussionmentioning
confidence: 88%
“…A B800/1020 antenna complex has been isolated and characterized [5] as consisting of three polypeptides differing in size [4,5]. In the case of purple non-sulfur bacteria a great number of lightharvesting polypeptides from various species have been isolated and their primary structures have been determined [13][14][15][16][17][18][19][20]. These antenna polypeptides exhibit a histidine residue in the central hydrophobic domain, assigned as the fifth ligand to the Mg atom of bacteriochlorophyll.…”
Section: Introductionmentioning
confidence: 99%